English as a Lingua Franca: Navigating the Imperatives through the Lens of Islamic Unity of Science Philosophy - Khodijah Asshofiah; Maryam; Masitoh Oktavia (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
This article explores the implications of English as a Lingua Franca (ELF) through the lens of Islamic Unity of Science (IUS) philosophy. Beginning with an introduction highlighting the importance of language in global communication, the literature review examines the historical evolution of ELF, its impact on linguistic diversity, and the challenges it poses to cultural identity. Using qualitative methodology, this research integrates insights from Islamic scholarship to enrich our understanding of linguistic diversity and cultural exchange. Hypothesizing that Islamic perspectives can offer an alternative framework for navigating the importance of ELF, this research synthesizes diverse perspectives to promote the principles of unity, diversity, and knowledge sharing. The conclusion underscores the importance of fostering dialogue and collaboration among diverse linguistic and cultural communities, emphasizing the need for linguistic equality and cultural inclusivity in a globalized world.